Study of factors affecting precast plant productivity in Singapore - Chan, Poh Ching. (2008)
This dissertation describes a study on the factors affecting precast plant productivity. A survey was conducted on 19 precast plants in Singapore during August 1998. The survey consisted of three parts. Part One consisted of collecting general information such as plant area, production capacity and types of precast components produced. The time spent on workshop drawing production, production planning and scheduling, scheduling of manpower and equipment were also included. Part Two of the survey was in the form of questionnaires to study the extent of the problems encountered at the precast plant related to labours, material and others factors affecting the precast plant productivity. The last part of the survey consisted of data collection on production time needed for the various activities during the production of different types of precast components. The total man-hours spent on producing each precast component by the different precasters would be used to compare the effectiveness in producing the precast components.